Pendidikan Adab Menurut Imam al-Nawawi dan Implementasinya di Pondok Pesantren Tahfidzul Qur’an SahabatQu - Adinda Dwi Adisti; Rukiyati Rukiyati (TSAQAFAH, 2021)
There are four educational concepts; purpose, curriculum, programs andevaluation. Education is a process of instilling the values of manners to becomea good human being. So that education can be said to prepare the values ofadab through varios strategies for achieving values of adab. The values of adabeducation need to be understood by educators and students who will use themas a guide during the learning process. Adab is a process of cultivating educationin a person. This study is based on the thoughts of Imam Abu Zakaria Yahyabin Syaraf al-Nawawi (Imam Nawawi) in his book al-Tibyân fî Âdâb Hamalah alQur’ân. This book discusses the manners of a learner in studying, understandingand teaching. The aims of this study is to find out how the management of adabeducation in the Pondok Tahfidzul Qur’an Pesantren SahabatQu (PPTQS) isbased on the thoughts of Imam Nawawi in his book. This study uses a qualitativedescriptive approach with the type of library research and content analysismethods which are used to analyze the strategy of achieving the values of adabof educators and students based on the thinking of Imam Nawawi. The results showed that it contains the concept of civilization education managements which contains planning, organizing, implementing and controlling adab which doesnot require instant time and must take a long time.